Uso de simulações computacionais para o ensino de Química em disciplinas do ensino superior - Mendes, Carla Cristina Alves (2025)
Abstract concepts in the subject of chemistry can be difficult for students to understand, as they cannot be visually perceived from something that is commonly experienced. Thus, the use of computer simulations in teaching can contribute for the understanding of these concepts, because it allows students to visualize what cannot be observed macroscopically. This study used molecular modeling simulations specifically computational chemistry software with students in order to generate visual representations of molecules. The use of WebMO software with semi-empirical quantum methodology was used to carry out the calculations and the AutoDock software to carry out with molecular docking mechanics methodology. A total of 14 Civil Engineering students from the first period and 157 Agronomy students from the first and second period of the 2021/1, 2021/2 and 2023/1 semesters carried out the computer simulations. The software served as a didactic resource to appropriate knowledge about chemical bonds, molecular geometry, frontier molecular orbitals and intermolecular interactions. Initially, the content was explained and then two activities were proposed to be developed in the WebMO software and two molecular docking in AutoDock4 between the enzyme ACCase and the herbicides clefoxidim and glyphosate. At the end of the semester, students answered a questionnaire about their use of WebMO. The WebMO mobile app and AutoDock4 software allowed the students to interact with the content as they carried out the simulation themselves. However, the difficulty encountered in this process is the fact that most of the specific software for computational chemistry is in English. Generally, specific software for computational chemistry is used to discover new compounds, new drugs, new methodologies for analyzing detection, the functioning of biomolecules, discoveries of new types of bonds and molecular interactions. They are used to develop groundbreaking work carried out by researchers from all over the world, and generally, most of this software is in English so that the language of these programs can be universalized, and it was precisely the language that was the greatest difficulty the students encountered in carrying out the simulations done by the Brazilian students. In both WebMO and AutoDock4 softwares, the visualization of chemical concepts helped the understanding of chemistry concepts. On the order hand, for the molecular docking, the students were able to understand the theory of chemistry in relation to the practice when they study ou practice the use of herbicide to combat weeds in the planting field. This study showed that students can use computer simulations and learn about the equations that govern them and learn with more easily chemical informations, and it created more interest and motivation in this chemical field. For teachers, computational chemistry software can act as a digital teaching resource to teach abstract chemistry concepts.